INVENTARISATION OF ORCHID TYPES (Orchidaceae) IN WEST TOMOHON AREA - Welan, Miracle Abbighael Varencia; Roring, Verawati Ida Yani; Lawalata, Helen Joan (Indonesian Biodiversity Journal, 2023)
This study aims to inventory orchid species in the West Tomohon area using the accidental sampling method of exploration in a predetermined place. Orchids are a type of flowering plant that comes from the Orchidaceae family. Each type of orchid has its own characteristics. Tomohon City has abundant natural resources, including ornamental plants such as orchids. Data on orchid diversity in West Tomohon Sub-district has never been reported. Orchid inventory is an activity that records the diversity of orchid species in an area. This research is descriptive-qualitative research. The results of this study have yielded 10 species of orchids belonging to nine genera in one family. The orchid species found in the West Tomohon area consist of Arachnis sp., Arundina graminifolia, Cattleya sp., Dendrobium biggibum, Dendrobium moschatum, Epidendrum secundum, Oncidium flexuosum, Phaius tankervilleae, Phalaenopsis amabilis, and Vanda arcuata. The most common orchid found in this area is the moon orchid, Phalaenopsis amabilis.